Comparative Efficacy of Pegylated Interferons α-2a and 2b in the Treatment of HBeAg-Negative Chronic Hepatitis B Infection - Karabay, O.; Tuna, N.; Esen, Ş. (Lippincott Williams & Wilkins, 2012)
INTRODUCTION: Interferons, pegylated interferons (PegIFN), and oral antivirals are used in the treatment of chronic hepatitis B (CHB) virus infection. The number of studies comparing the efficacy of PegIFNs in the treatment of HBe antigen-negative CHB is rather limited. In this trial, the efficacy of two PegIFN products used in the treatment of CHB is compared. Methods: Study data were obtained from 16 tertiary healthcare service centers located in various areas of Turkey. Data of patients who were consecutively treated with PegIFN α-2a or α-2b for CHB were recorded retrospectively. Hepatitis B virus DNA and liver enzymes were analyzed at the beginning of the treatment and during weeks 12, 24, 48, and 72. A P-value less than 0.05 was considered to be significant. Results: A total of 155 patients were enrolled in this trial. Two cases were excluded because of insufficient data. Among the remaining 153 patients, 81 (53%) patients were in the PegIFN α-2a group and 72 (47%) patients were in the α-2b group. Treatment success was found to be 17.2% for the PegIFN α-2a group and 18.0% for the PegIFN α-2b group (P>0.05). In terms of efficacy (weeks 24, 48, and 72), there were no significant differences between the groups (P>0.05). Conclusion: According to our results, for HBe antigen-negative CHB cases, the response rate during the sixth month after the treatment with PegIFN was determined to be ∼17%. No difference was found between the efficacy rates of the two PegIFN products used in the treatment of HBe antigen-negative CHB. © 2012 Wolters Kluwer Health | Lippincott Williams & Wilkins.
Keywords: Chronic Hepatitis B; Pegylated Interferon; Treatment